Pete the Kitty's outdoor art project - Dean, Kim, 1969-; Dean, James, 1957- (2023)
"Pete the Kitty loves art class. But when the project is to go outside and make art from nature, Pete isn't sure what to create. Then inspiration strikes and Pete realizes that nature art is cooler than he ever imagined"--
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Pete, -- the Cat (Fictitious character); Cats -- Juvenile fiction; Art -- Juvenile fiction; Nature in art -- Juvenile fiction; Humorous stories; Picture books; JUVENILE FICTION -- Animals -- Cats; JUVENILE FICTION -- Art & Architecture; JUVENILE FICTION -- Readers -- Beginner; Art; Cats; Nature in art; Cats -- Juvenile fiction; Art -- Juvenile fiction; Nature in art -- Juvenile fiction; Cats -- Fiction; Art -- Fiction; Nature in art -- Fiction; Easy readers; picture books; FICTION / Animals / General. -- JUV002000; Fiction; Humorous fiction; Juvenile works; Picture books; Humorous fiction; Humorous fiction; Picture books